Pharmaceutical consultation as a tool to improve health outcomes for patients with type 2 diabetes - Arnaldo Zubioli; Maria Angélica Rafaini Covas Pereira da Silva; Raquel Soares Tasca; Rui Curi; Roberto Barbosa Bazotte (Universidade de São Paulo, 2013)
This study develops and evaluates a pharmaceutical consultation program (PCP) to improve treatment for Type 2 diabetes patients (T2DP) and reduce risk factors for diabetic complications with possible application in other chronic diseases. We recruited T2DP receiving conventional medical treatment but with fasting glycemia >140mg/dl and/or glycated hemoglobin >7%. The PCP includes strategies obtained from Dader's method, the PWDT (Pharmacist's Workup of Drug Therapy method) model of pharmaceutical care, the SOAP (Subjective data, Objective data, Assessment, and Plan of care) method, and concepts based on a nursing care model. The PCP evaluated lifestyle, pharmacotherapy and monitoring it using laboratory tests, vital signs, and anthropometry. These procedures were repeated every 4 months for 1 year. Data obtained in each consultation were used to provide patient education focusing on healthy lifestyles and medications. Fifty patients completed the PCP. There were reductions in glycemia (P<0.0001), glycated hemoglobin (P=0.0022), cholesterolemia (P=0.0072), triacylglycerolemia (P=0.0204) and blood pressure (P<0.0001). Increased concordance with drug treatment and correction of drug-related problems contributed to improved treatment. We can therefore conclude that our PCP was suitable for improving health outcomes in T2DP by reducing risk factors for diabetic complications. Neste estudo, desenvolvemos e avaliamos um programa de consulta farmacêutica (PCF) visando melhorar o tratamento de pacientes diabéticos tipo 2 (PDT2) e reduzir os fatores de risco de complicações diabéticas com possibilidade de aplicação em outras doenças crônicas. Para alcançar este propósito, PDT2 recebendo tratamento médico convencional, apresentando glicemia de jejum > 140 mg/dl e/ou hemoglobina glicada >7% foram selecionados. O PCF inclui estratégias obtidas a partir do método de Dader, do modelo de cuidados farmacêuticos PWDT (Pharmacist's Workup of Drug Therapy method), do método SOAP (Subjective data, Objective data, Assessment, and Plan of care) e conceitos baseados em um modelo de cuidados em enfermagem. O PCF avaliou o estilo de vida, farmacoterapia e seu monitoramento através de exames laboratoriais, sinais vitais e antropometria. Estes procedimentos foram repetidos a cada 4 meses durante 1 ano. Os dados obtidos em cada consulta possibilitaram oferecer educação focada no estilo de vida e uso de medicamentos. Para os 50 pacientes que concluiram o PCF houve redução da glicemia (P < 0.0001), hemoglobina glicada (P = 0.0022), colesterolemia (P = 0.0072), triacilgliceridemia (P= 0.0204) e pressão arterial (P < 0.0001). O aumento da concordância e a correção dos problemas relacionados a medicamentos contribuíram para melhoria do tratamento. Assim, podemos concluir que o PCF foi adequado para melhorar a saúde de PDT2 ao reduzir fatores de risco de complicações diabéticas.